Association of Dietary Ganglioside Intake and Gastrointestinal Discomfort Among Chinese Urban Adults: A Cross-sectional Study in Eight Cities of China (P18-050-19). (13th June 2019) - Wu, Wei; Zhao, Ai; Szeto, Ignatius Man-Yau; Wang, Yan; Feng, Haotian; Li, Ting; Zhang, Jian; Wang, Meichen; Tan, Shengjie; Zhang, Yumei
Abstract: Objectives: To profile dietary ganglioside intake and explore its association with gastrointestinal health among Chinese adults. Methods: A cross-sectional survey was conducted among urban adults from eight Chinese cities. Total of 1491 individuals remained in the final analysis. Gastrointestinal symptoms were evaluated by the total score of Gastrointestinal Symptoms Rating Scale (GSRS) and individual scores of five dimensions in GSRS, consisting of dyspepsia, diarrhea, abdominal pain, gastroesophageal reflux and constipation. Dietary intake of ganglioside was calculated by combining data derived from a single 24-hour recall with the database of ganglioside content in food. The association between ganglioside intake and GSRS was examined using multiple linear regression analysis. Results: Dietary ganglioside intake among whole population was 3.10(1.34, 5.24) mg per day. Women ( P  < 0.001), individuals above 45 years old ( P  < 0.001), with lowest household monthly income ( P  < 0.001) or residing in northern cities ( P  < 0.001) tended to ingest less ganglioside. The food categories contributing to daily ganglioside intake were ranked in a descending order as livestock and poultry meat (53.05%), dairy products (25.45%), eggs (16.40%), fish (2.90%) and others (2.20%) at a whole population level. Multiple linear regression analysis exhibited individual scores of both abdominal pain ( P  = 0.041) and gastroesophageal reflux ( P  = 0.002) were inversely associated with ganglioside intake in the crude models. After adjustment for potential confounders including gender, self-rated health condition, occupational status, and levels of household monthly income, only the relationship between gastroesophageal reflux ( β = −0.006, P  = 0.016) and ganglioside intake still remained significant. No association of the total score of GSRS with ganglioside intake was observed in both unadjusted and adjusted models. Conclusions: This cross-sectional study implied the link existed between gastrointestinal symptoms, involved with the early stage of some serious diseases, such as ulceration, Inflammatory Bowel Disease, and dietary intake of ganglioside among Chinese adults, which warrants further longitudinal studies. Funding Sources: This research received no external funding.